Comprehensive characterization and valorization potential of Amazonian Sacha inchi (Plukenetia volubilis L.) seeds, oil, and oilcake by-products for sustainable food applications - Alejandro Ruiz, Fernando E.; Ortega Jácome, Julio F.; Mora, José R.; Landázuri, Andrea C.; Vásconez Duchicela, Paola; Vásconez Espinoza, Julio; Beltrán-Ayala, Pablo; Andrade-Cuvi, María J.; Alvarez-Suarez, José M. (Frontiers in Nutrition, 2025)
BackgroundSacha inchi (Plukenetia volubilis L.), a native oilseed from the Amazon region, has attracted increasing attention for its nutritional richness and potential applications in functional foods. However, detailed studies on the characterization and valorization of its seeds, oil, and defatted oilcake by-products from the Ecuadorian Amazon remain scarce. This study evaluates the bromatological, chemical, bioactive, and techno-functional properties of Sacha inchi seeds and their by-products from the Ecuadorian Amazon to assess their potential as functional ingredients in bakery applications.MethodsBromatological composition and color of Sacha inchi seeds and oilcake flour were determined. Mineral content was analyzed using inductively coupled plasma optical emission spectrometry (ICP-OES). Techno-functional properties-including swelling capacity (SC), water absorption capacity (WHC), water retention capacity (WRC), and oil holding capacity (OHC)-were assessed in oilcake flour. Total polyphenol content and antioxidant capacity (DPPH and FRAP assays) were evaluated. The oil was analyzed for physicochemical quality and fatty acid composition using gas chromatography-mass spectrometry (GC-MS).ResultsSacha inchi seeds were primarily composed of fat, followed by protein. In contrast, the defatted oilcake flour showed increased protein content, notable fiber levels, and high mineral concentrations-particularly calcium (2,634 mg/kg), magnesium (3,692 mg/kg), potassium (7,684 mg/kg), and phosphorus (9,140 mg/kg). Polyphenol content (50.53 mg GAEq/100 g) and antioxidant capacity (DPPH: 36.08 mM TEq/g FW; FRAP: 62.52 mM TEq/g FW) were largely retained after oil extraction. The oil was rich in essential fatty acids, notably α-linolenic acid (46.92%) and linoleic acid (38.09%), though its oxidative instability requires attention. Techno-functional evaluation of the oilcake flour showed moderate swelling capacity (3.47 ± 0.12), WHC (4.16 ± 0.63), WRC (3.50 ± 0.24), and low OHC (1.02 ± 0.05), which may affect hydration, freshness, and texture in bakery formulations. Overall, the oilcake flour outperformed wheat flour in protein, fiber, and mineral content, supporting its potential in developing nutritionally enhanced baked goods.ConclusionsSacha inchi oil and its defatted oilcake flour show high nutritional quality and functional potential. Their incorporation into food formulations could promote the development of healthier, sustainable products aligned with circular economy principles.